2000
DOI: 10.1074/jbc.275.13.9749
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Activation Function for NAB Proteins in EGR-dependent Transcription of the Luteinizing Hormone β Gene

Abstract: The EGR1/NGFI-A transcription factor directly activates the luteinizing hormone ␤ (LH␤) subunit promoter, and female mice lacking EGR1 are infertile due to LH␤ deficiency. The NGFI-A-binding proteins NAB1 and NAB2 are corepressors of EGR1/NGFI-A and of the related proteins EGR2/Krox20 and EGR3. Here we report that at certain promoters, including LH␤, NAB proteins display a novel ability to stimulate EGR-directed transcription. NAB coactivation requires the conserved NCD2 protein domain, previously implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 62 publications
4
84
1
Order By: Relevance
“…The Ϫ1523 to ϩ23 TRAIL promoter luciferase reporter deletion plasmids were described previously (37). Luciferase reporter assays were performed as described (38,39). Mutation of the forkhead binding site in the Ϫ165 to ϩ23 TRAIL promoter luciferase construct was generated using the QuikChange kit (Stratagene Corp.) and complementary primers 5Ј-GAGGAGCTTCA-GACAGAGACCCTCCAGACCAACGCCAACG-3Ј and CGTTGGCGTT-GGTCTGGAGGGTCTCTGTCTGAAGCTCCTC.…”
Section: Methodsmentioning
confidence: 99%
“…The Ϫ1523 to ϩ23 TRAIL promoter luciferase reporter deletion plasmids were described previously (37). Luciferase reporter assays were performed as described (38,39). Mutation of the forkhead binding site in the Ϫ165 to ϩ23 TRAIL promoter luciferase construct was generated using the QuikChange kit (Stratagene Corp.) and complementary primers 5Ј-GAGGAGCTTCA-GACAGAGACCCTCCAGACCAACGCCAACG-3Ј and CGTTGGCGTT-GGTCTGGAGGGTCTCTGTCTGAAGCTCCTC.…”
Section: Methodsmentioning
confidence: 99%
“…Originally, they were identified as corepressors of EGR-mediated transcription by direct binding to Egr-1, Egr-2 and Egr-3 [18,19]. Subsequently, it has been shown that NAB2 can also co-activate Egr-mediated transcription [20]. Indeed, our group has recently identified NAB2 as a novel co-activator of T cell function by enhancing Egr-1-mediated IL-2 production.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a specific physiologically relevant frequency range of receptor stimulation on the order of 1 pulse/h preferentially induces the luteinizing hormone beta subunit (LH␤) gene (1,2). Although downstream signal transduction mediators (such as JNK and ERK) and a number of transcription factors (including Egr1, SF1, and NAB1) have been implicated in modulation of the LH␤ promoter (3)(4)(5)(6), the available data do not explain why the induction of LH␤ requires specific patterns of GnRHR activation.…”
mentioning
confidence: 99%